Physical activity, sedentary time and bone tissue: effects of an 8-months interdisciplinary program with overweight/obese children - Mello, Júlio Brugnara (2019)
Moderate to vigorous physical activity plays a recognized osteogenic effect on bone. Moreover, sedentary time, and fat accumulation are unfavorable to bone health. Our study aimed (1) to examine changes in body composition, bone tissue, physical activity, and sedentary time; and (2) to explore whether changes in physical activity intensities and in sedentary time are associated with changes in bone outcomes after a school-based interdisciplinary intervention program. A total of 53 overweight/obese students (10.6 ± 3.5 year-olds; 26 girls) participated in physical activity classes. Bone area, bone mass, and bone mineral density z-score, body composition (fat mass, fat lean mass), physical activity, sedentary time and potential confounders (vitamin D and maturational status) were assessed at baseline, and 8 months later. General Linear Models were carried out and significance level was set at 5%. Changes in moderate to vigorous physical activity were positively correlated with changes in all bone mass indicators. We observed a significant overall effect of the intervention on bone mineral density z-score changes, however after adjustments for changes in sedentary time and moderate to vigorous physical activity, no effect was observed. Finally, variations in sedentary time and in moderate to vigorous physical activity play an important role in bone mass density in those participants of the interdisciplinary program.